Sugar cane, peasants and panel, emergency of the sweet territory in the east antioqueño - Quintero Hernandez, Jose Anibal (2019)
In the East of Antioquia, hydroelectric projects, peasant population and armed conflict cross each other, generating dynamics of deterritorialization. This article analyzes the processes of conformation of a possible new territoriality that assembles the peasant and the food production as part of a process of restitution of life’s worlds in a post-conflict situation in Colombia. The research was based on an ethnographic approach with two ‘panela’ (sugar cane candies) producers’ organizations, departing from a social actors perspective, and identifying components (material or not) linked to reterritorialization processes. The paper finally identifies an alliance between sugar cane, peasant and the ‘panela’, which is vital for the emergence of the 'Sweet Territory', where socio-material dynamics are established, enabling life and restoring identities in their affective processes and inherent corporalities.